Benchmarking w realizacji strategii przedsiębiorstwa - Kowalak, Robert (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In this article is presented relationship between benchmarking and strategy of enterprise. Benchmarking should be popularized within small and medium-sized enterprises, which have own small capital. They have to restrict the risk with their knowledge. Knowing competition let easier look in the future in difficult market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 147-154